PLURALISME DEMOKRASI POLITIK DI INDONESIA - M. Dian Hikmawan (Journal of Governance, 2017)
In defining citizenship, we need an pre-position that places everything in an equal position. This means that politics must be able to bridge the citizen's equal behavior. Under these circumstances, the possibility of political life becomes the key for understanding everyday political events. This paper discussing how citizens should struggle in politics in Indonesia to achieve equality for these citizenship. Modern democracy which requires general rationality becomes the problem that arises when the general rationality is transformed into a hegemonic that injures the rights of other citizens. The unique political life of the citizens is reduced by the common sense of rationality, At least this paper cultivates the exclusion behavior of citizens in daily life.